Treatments in psoriasis: from standard pharmacotherapy to nanotechnology therapy - Zhu, Baohua; Jing, Mingyi; Yu, Qianying; Ge, Xiaopei; Yuan, Fan; Shi, Lanhui (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Psoriasis is a genetic chronic disease mediated by the immune system with systemic and cutaneous manifestations that can significantly deteriorate patients’ quality of life. Two–three percent of the population worldwide suffer from psoriasis and it imposes a substantial economic burden on patients. The aetiology is mainly related with genes and environmental factors. The pathophysiology of psoriasis is characterized by T cells and dendritic cells, antimicrobial peptides, genetic predispositions, lipoprotein-2, galactosin-3, fractalkine, vaspin, and human neutrophilic peptides, etc. in the progression of psoriasis. For patients with psoriasis, the traditional treatments include corticosteroids, vitamin D3 analogues, calcineurin inhibitors, methotrexate, cyclosporine, acitretin, phototherapy, and biological agents, etc. Nanodermatology is an emerging, multidisciplinary science that is gaining increasing recognition in the treatment of psoriasis. This review provides a summary of the pathophysiology, epidemiology, clinical diagnosis, and classical pharmacotherapy of psoriasis. The review also summarizes different nanotechnology therapies for effective treatment of psoriasis.